DAYCARE PRIVATE SPACE DESIGN FOR COVID-19 PREVENTION - hasby muhammad ihwan; Rizka Rachmawati (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Child care is now a priority for parents in an effort to help optimize the development of their children, both at stages of physical, cognitive and social and emotional development. In the state of the covid 19 scourge currently sweeping the world, daycare is a concern for parents who send their children away. Thus, this study addresses the interior design of private daycare spaces to support the development process of children according to the daycare center in the middle of the covid 19 epidemic, which aims to provide distance and limit movement between children of the daycare in accordance with government recommendations. This study uses qualitative methods, in particular through the analysis of field observations, but also studies of the literature, which aim to know how to design a good daycare in accordance with the standards in force during the covid 19 epidemic, to respond to user needs. This research should be an alternative solution for owners of daycares that will remain open during the covid 19 outbreak, so that with the design of a measurable and well-designed and appropriate private space, it will build the image and belief of parents that the daycare during the covid 19 outbreak will remain safe and comfortable to use. Keywords: early childhood education, private room, covid-19 pandemic